PENGARUH PEMBERDAYAAN, PENGEMBANGAN KARIR, DAN LINGKUNGAN KERJA TERHADAP KINERJA DENGAN MEDIASI MOTIVASI (STUDI PADA CV. BUANA RAYA SEMARANG) - 11.42.02.0110, Budi Susatyo (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research is aimed to explain the effects of empowerment, career development and working environment on employeeâs performance with the motivation mediation in CV Buana Raya Semarang. This research is conducted in t census method with the population of all the employees of CV Buana Raya. Survey data is collected from 77 employees with the method of collecting data by giving quesionare ( list of questions ) to the employees. To test the validity of the data gatheredit uses validity test ( factor analyze ) and reliability test with the coefficient alpha . And the statistictest which is used is regression R2 and t test to test the significancy ofregression coefficient. The result of this research shows that empowerment, career development, and working environment are significantly influence the employeeâs motivation. This research also shows that empowerment, career development and working environment donât influence the employeesâ performance since they canât interfere the three dimensions of performance i.e personal, psychology, and organisation. On the other hand motivation influence significantly to the employeesâ performance. The conclusion is empowerment, career development and working enviroment donât directly influence the performance but with the motivation mediation those three variables can influence the perfoemance of employees in CV. Buana Raya Semarang. Keywords : Empowerment, Career Development, Working Environment, Motivasion, and Performance